The Influence Of The Level Of Knowledge And Clean And Healthy Living Behaviors On The Incidence Of Scabies In The Al-Ibtikary Islamic Boarding School, Karangan Trenggalek District - Joko Sutrisno; Anida Fadila Putri (Universitas STRADA Indonesia, 2025)
Scabies is a disease caused by mites/lice of the Sarcoptes Scabiei hominis variety. Scabies is easily spread either directly by sufferers or indirectly through clothes, bed sheets, towels. Islamic boarding schools are one of the places at risk of transmitting scabies. This study aims to analyze the influence of the level of knowledge and clean and healthy living behavior on the incidence of scabies at the Al-Ibtikary Islamic Boarding School Karangan Trenggalek.This research design uses correlative descriptive with a cross sectional approach. The total sample was 86 respondents using simple random sampling technique. The research instrument used a questionnaire. The independent variables are the level of knowledge and clean and healthy living behavior. The dependent variable is the incidence of scabies. The research results showed that out of a total of 86 respondents, 38 respondents (44.2%) were known to have a sufficient level of knowledge. Respondents who had sufficient clean and healthy living behavior were 48 respondents (55.8%). Respondents with scabies incidents were 54 respondents (62.8%).Based on the results of the logistic regression test, it shows the level of knowledge with a P value of 0.001 (< 0.05) and clean and healthy living behavior with a P value of 0.000 (< 0.05), meaning that there is an influence of the level of knowledge and clean and healthy living behavior on the incidence of scabies. at the Al-Ibtikary Karangan Trenggalek Islamic Boarding School.In this study, clean and healthy living behavior was the most dominant factor influencing the incidence of scabies. The better the clean and healthy living behavior of a student, the more indirectly it can prevent the incidence of scabies. Apart from that, it will also have a good impact on the order of clean and healthy living behavior in Islamic boarding schools.